Cultural Da'wah Strategy in Preserving Local Wisdom of the Sundanese Wiwitan Ngasa Tradition in Jalawastu: Strategi Dakwah Kultural dalam Pelestarian Kearifan Lokal Tradisi Ngasa Sunda Wiwitan di Jalawastu - Nanda Arinal Haqi; Agus Riyadi; Abdul Karim (Alhadharah: Jurnal Ilmu Dakwah, 2025)
The social reality of indigenous communities facing pressures from social change and modernization has the potential to undermine the sustainability of local traditions while simultaneously generating tensions between religion and culture. This study aims to analyze how da‘wah practices and strategies interact with the Ngasa tradition in the social life of the community, as well as the strategies employed to preserve local wisdom values. The research adopts a qualitative approach with a field research design. Data were collected through observation, interviews, and documentation. Data analysis was conducted using a descriptive–interpretative method through the stages of data reduction, data presentation, and conclusion drawing. The findings indicate that cultural da‘wah is carried out in a contextual and dialogical manner by positioning tradition as a medium for the internalization of religious values rather than as an object of rejection. This approach strengthens social harmony, reinforces cultural identity, and sustains the Ngasa tradition amid modernization. These findings underscore the importance of cultural da‘wah as a relevant, inclusive model of religious outreach rooted in the local wisdom of indigenous communities. KEYWORDS: cultural da’wah; local wisdom; Ngasa tradition; Sunda Wiwitan; indigenous community